Multiplexed Microsphere-Based Flow Cytometric Assay to Assess Strain Transcending Antibodies to Plasmodium vivax Duffy Binding Protein II Reveals an Efficient Tool to Identify Binding-Inhibitory Antibody Responders - Alves, Jéssica R. S.; de Araújo, Fernanda F.; Pires, Camilla V.; Teixeira-Carvalho, Andréa; Lima, Barbara A. S.; Torres, Letícia M.; Ntumngia, Francis B.; Adams, John H.; Kano, Flora S.; Carvalho, Luzia H. (Frontiers in Immunology, 2021)
Malaria remains a major public health problem worldwide, and Plasmodium vivax is the most widely distributed malaria parasite. Naturally acquired binding inhibitory antibodies (BIAbs) to region II of the Duffy binding protein (DBPII), a P.vivax ligand that is critical for reticulocyte invasion, are associated with a reduced risk of clinical malaria. Owing to methodological issues in evaluating antibodies that inhibit the DBPII–DARC interaction, a limited number of studies have investigated DBPII BIAbs in P. vivax-exposed populations. Based on the assumption that individuals with a consistent BIAb response are characterized by strain-transcending immune responses, we hypothesized that detecting broadly reactive DBPII antibodies would indicate the presence of BIAb response. By taking advantage of an engineered DBPII immunogen targeting conserved DBPII neutralizing epitopes (DEKnull-2), we standardized a multiplex flow cytometry-based serological assay to detect broadly IgG antibodies. For this study, a standard in vitro cytoadherence assay with COS-7 cells expressing DBPII was used to test for DBPII BIAb response in long-term P. vivax-exposed Amazonian individuals. Taken together, the results demonstrate that this DBPII-based multiplex assay facilitates identifying DBPII BIAb carriers. Of relevance, the ability of the multiplex assay to identify BIAb responders was highly accurate when the positivity for all antigens was considered. In conclusion, the standardized DBPII-based flow cytometric assay confirmed that DBPII-BIAb activity was associated with the breadth rather than the magnitude of anti-DBPII antibodies. Altogether, our results suggest that multiplex detection of broadly DBPII-reactive antibodies facilitates preliminary screening of BIAb responders.